Non-Litigation Paradigm in Medical Dispute Resolution: An Indonesian Perspective - Prima Maharani Putri (Kosmik Hukum, 2024)
This article aims to analyze the non-litigation paradigm in resolving medical disputes between doctors and patients based on the applicable laws and regulations in Indonesia, along with its implications for improving the quality of health services. This research approach is with a normative juridical method with a statute approach and a conceptual approach. The results of the study revealed that the doctor's relationship that started from a paternalistic relationship has shifted to a partnership. This is evidenced by the regulation of therapeutic transactions and informed consent in every health service provided. Health services, which according to Law No. 17 of 2023 concerning Health are in the form of health efforts (inspanning verbintenis), allow the risk of doctor-patient medical disputes. This law is also the basis for resolving medical disputes between doctors and patients. The law in article 310 stipulates that the resolution of medical disputes first through alternative dispute resolution outside the court (non-litigation). The paradigm of resolving medical disputes through non-litigation can make the doctor-patient relationship more qualitative, because of the win-win solution principle used. A good doctor-patient relationship will also have a good impact on improving the quality of health services provided. Doctors and patients are in their best position as providers and recipients of health services because the good name of doctors and patients is maintained and medical disputes can be resolved with the principle of kinship, without having to waste a lot of money, time and energy.Keywords: Medical Disputes, Non-Litigation, Doctor-Patient